Impact of early Kasai portoenterostomy on short-term outcomes of biliary atresia: A systematic review and meta-analysis - Yang, Changzhen; Ke, Meng; Zhou, Yan; Xu, Hang; Diao, Mei; Li, Long (Frontiers in Surgery, 2022)
Background: Good outcomes of biliary atresia (BA) are conventionally achieved after early Kasai portoenterostomy(KP). However, in some recent literatures, there are discrepancies in the influence of age at KP on postoperative short-term prognosis. The aim of this meta-analysis was to evaluate the effects of earlier KP on short-term surgical prognosis of BA and clarify these discrepancies in recent studies. Methods: To identify related studies, PubMed, Embase, Web of Science, Cochrane, and the Chinese National Knowledge Infrastructure database were searched up to March 2022. Data for the impact of age at Kasai portoenterostomy on clinical prognosis were extracted, including jaundice clearance rate and native liver survival rate. Results: Fourteen articles were included in the present study, which involve a total of 3276 patients with BA who underwent KP. Compared with patients older than 91 days of age, patients 90 days of age or younger exhibited significantly better jaundice clearance rate (JCR) (OR, 3.05; 95% CI, 2.23-4.17; P<0.001) and more favorable native liver survival rate(NLSR) (OR, 1.72; 95% CI, 1.37-2.15; P<0.001). The NLSR of patients younger than 60 days of age were significantly higher than those of patients with 61 to 90 days of age (OR, 1.41; 95% CI, 1.18-1.68; P<0.001). There was no significant difference in JCRs of patients 60 days of age or younger and patients 61 to 90 days of age (OR, 1.31; 95% CI, 0.95-1.81; P=0.10). Among patients 30 days of age or younger, 31 to 45 days of age, and 46 to 60 days of age, there were also no significant differences in JCR. Conclusion: A significantly better short-term jaundice clearance and native liver survival was achieved among patients with BA treated using a KP at ≤90 days of age compared to those treated at >90 days of age. There was no further improvement in short-term JCR when the procedure was performed at ≤60 days compared to 61 to 90 days of age. However, treatment at ≤60 days of age was associated with a significant improvement in NSLR. Therefore, the timing of KP does exert an important effect on short-term clinical outcomes of patients with BA.